Zinc borate doped single crystal, growth method thereof and laser crystal

Through the growth method of doped zinc borate single crystal, the waste heat problem generated by laser crystals during laser generation and amplification is solved, and the laser crystal with low thermal expansion and high thermal conductivity is achieved, which significantly improves the thermal stability of the laser and output laser. Power and mass.

CN119465403AActive Publication Date: 2025-02-18TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411453542.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

Existing laser crystals are prone to generate waste heat during laser generation and amplification, resulting in thermal effects such as thermal lensing, thermal distortion and thermal diffraction loss, affecting the quality and power of the laser.

Method used

Using the growth method of doped zinc borate single crystal, large-size and high-quality ZBO:Mn2+ single crystals were grown by preparing a melt of ZBO:Mn2+ and slowly cooling with platinum wire.

Benefits of technology

The ZBO:Mn2+ single crystal grown by this method has low isotropic thermal expansion coefficient, high thermal conductivity, excellent optical performance and high optical stability, which significantly improves the thermal stability of the laser and output laser. Power and mass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a doped zinc borate single crystal, a growth method thereof and a laser crystal. The method comprises the following steps: mixing raw materials containing manganese, zinc and boron, heating to a first temperature, stirring, and cooling to a second temperature to obtain a melt; a platinum wire is immersed below the liquid level of the melt and then slowly cooled, and the platinum wire on which crystals grow is extracted from the melt and then subjected to first cooling; taking all or part of the obtained crystals as seed crystals, immersing the seed crystals below the liquid level of the melt, setting the rotating speed of the seed crystals, slowly cooling, extracting the crystals from the melt, and then cooling for the second time; and taking all or part of the obtained crystals as seed crystals, and repeating the crystal growth process at least once. The zinc borate doped single crystal prepared by the method has the advantages of low thermal expansion coefficient (isotropy), high thermal conductivity, long fluorescence lifetime, excellent absorption cross section and excellent emission cross section, has excellent optical performance and thermophysical performance, can significantly improve the thermal stability and laser output performance of a laser, and has good laser technology application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser crystals, and in particular to a doped zinc borate single crystal and a growth method thereof, and a laser crystal. Background Art

[0002] Laser crystals, as the medium for laser generation and amplification, are the key basic materials for all-solid-state lasers. In the process of laser generation and amplification, waste heat will inevitably be generated in the laser crystal, which will lead to unnecessary thermal effects such as thermal lensing, thermal distortion and thermal diffraction loss, seriously affecting the quality and power of the generated laser. Commonly used laser crystals, mainly oxides and fluorides, rely heavily on thermal management equipment to offset thermal effects to ensure the quality of the generated laser. However, the considerable thermal expansion and low thermal conductivity in these crystals restrict the limits of the output laser quality that can be achieved by thermal management, which is increasingly unable to meet the growing requirements of laser quality and power in the evolving laser technology. Exploring laser crystals with the lowest possible (preferably isotropic) thermal expansion and the highest possible thermal conductivity is an urgent need for the development of laser technology. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a doped zinc borate single crystal and a growth method thereof, and a laser crystal.

[0004] In a first aspect, the present invention provides a method for growing a doped zinc borate single crystal, comprising:

[0005] 1) Preparation of ZBO:Mn 2+ melt: mixing raw materials containing manganese, zinc and boron, heating to a first temperature, stirring, and cooling to a second temperature to obtain a melt;

[0006] 2) Crystal growth: immersing the platinum wire below the liquid surface of the melt and then slowly cooling it, and then taking out the platinum wire with the crystal grown thereon from the melt and performing a first cooling;

[0007] 3) Secondary growth of crystals: using all or part of the crystals obtained in step 2) as seed crystals, immersing them below the liquid surface of the melt, setting the seed crystal rotation speed and slowly cooling them, and performing a second cooling after taking the crystals out of the melt;

[0008] 4) Repeated crystal growth: using all or part of the crystal obtained in step 3) as a seed crystal, repeating the crystal growth process of step 3) at least once.

[0009] The present invention provides a method for growing a doped zinc borate single crystal with excellent performance, which can grow large-sized and high-quality ZBO:Mn 2+ Single crystal. ZBO:Mn 2+The single crystal emits green light under ultraviolet light, and has a low, isotropic thermal expansion coefficient, high thermal conductivity, long fluorescence lifetime, excellent absorption cross section and emission cross section, which significantly improves the thermal stability of the laser. 2+ Single crystals have excellent optical and thermophysical properties, which can effectively improve the power and quality of the output laser and extend the service life of the laser. They are suitable for high-power lasers and high-optical quality laser technology applications.

[0010] Preferably, in step 1), the first temperature is 1000-1100° C.; preferably, the temperature is raised to 1000-1100° C. at a rate of 0.5-5° C. / min, and stirred at a stirring rate of 5-50 rpm with a platinum stirring paddle for 2-10 days.

[0011] Further preferably, in step 1), the second temperature is 900-1000° C.; preferably, it is reduced to 900-1000° C. at a rate of 0.1-20° C. / h.

[0012] Further preferably, in step 1), in the raw materials, the manganese source is MnCO3 and / or MnO, the zinc source is ZnO, Zn2(OH)2CO3 and / or Zn2(CH3COO)2·2H2O, and the boron source is B2O3 and / or H3BO3; the ZBO:Mn 2+ Zn4B6O 13 :Mn 2+ , Mn 2+ The ion doping concentration is 0.1% to 30%, preferably 1% to 10%. According to the present invention, in the doped zinc borate single crystal, the doping concentration is the molar percentage of the doped manganese element to the zinc element in the zinc borate.

[0013] According to the present invention, the purity of the raw materials used is 99.99%. The raw materials are fully ground and mixed and filled into a platinum crucible, and then subsequently processed in a programmed crystal growth furnace.

[0014] More preferably, in step 2), the immersion depth is 1 to 5 mm below the liquid surface of the melt.

[0015] More preferably, in step 2), the slow cooling is performed at a rate of 0.1 to 1° C. / day for 3 to 20 days.

[0016] Further preferably, in step 2), the platinum wire with the crystals grown thereon is taken out from the melt, and the platinum wire with the crystals grown thereon is raised to 1 to 5 cm above the melt surface.

[0017] More preferably, in step 2), the first cooling is to cool to room temperature at a rate of 1 to 20°C / h.

[0018] Further preferably, it should be noted that, if the corresponding ZBO:Mn 2+ The single crystal can be directly used as a seed crystal. This solution and its extension solution are also within the protection scope of the present invention.

[0019] The ZBO:Mn obtained by the present invention 2+ Single crystals have low, isotropic thermal expansion coefficients, high thermal conductivity, excellent optical properties, and high optical stability when the temperature changes. They can quickly dissipate heat and reduce optical distortion caused by thermal expansion in laser technology. In particular, the specific growth methods, growth temperatures, growth times, and rotation speeds of crystal growth, secondary growth, and repeated growth, as well as the specific cooling speed and time, have been further optimized. These conditions further ensure the purity and quality of the crystals and significantly improve the various properties of laser crystals.

[0020] Preferably, in step 3), the immersion depth is 1 to 5 mm below the liquid surface of the melt.

[0021] More preferably, in step 3), the rotation speed of the seed crystal is 1 to 30 rpm, and the slow cooling is performed at a rate of 0.1 to 1° C. / day for 3 to 20 days.

[0022] Further preferably, in step 3), the crystals are taken out from the melt, and the grown crystals are raised to 1 to 5 cm above the melt surface.

[0023] More preferably, in step 3), the second cooling is to cool to room temperature at a rate of 1 to 20°C / h.

[0024] Further preferably, step 3) also includes reheating the raw material reagent after cooling in step 2) to the first temperature and stirring it, cooling it to the second temperature to obtain a melt again; preferably, the temperature is raised to 1000-1100°C at a rate of 0.5-5°C / min, and stirred at a stirring rate of 5-50rpm with a platinum stirring paddle for 2-10 days; then the temperature is reduced to 900-1000°C at a rate of 0.1-20°C / h to obtain the melt.

[0025] More preferably, in step 3) and / or step 4), the transparent and uniform part of the grown crystal is used as the seed crystal. In the present invention, the transparent and uniform part refers to the part of the crystal that is transparent and uniform in color.

[0026] Further preferably, in step 4), the crystal growth process is repeated 1 to 10 times, preferably 3 to 10 times.

[0027] The present invention processes raw materials and grows crystals under optimal conditions, performs secondary crystal growth on the obtained seed crystals, uses the transparent uniform part as the seed crystals for repeated growth, and further obtains higher quality doped crystals by optimizing the process and process parameters. The preparation process of the present invention is simple to operate, and can greatly improve the crystal quality by optimizing the process parameters. The optical properties and thermophysical properties of the doped zinc borate single crystal are further improved by optimizing the process and parameters.

[0028] In a second aspect, the present invention provides a doped zinc borate single crystal, which is obtained by the above-mentioned growth method of the doped zinc borate single crystal.

[0029] Further preferably, the doped zinc borate single crystal has green light emission under ultraviolet light irradiation; preferably, the luminescence properties of the doped zinc borate single crystal are: emission peak central wavelength: 530-550nm, emission peak half-peak width: 30-50nm, excitation band: 200-500nm, fluorescence lifetime at 300K: 10-20ms, emission cross section: 10 -25 ~10 -21 cm -2 , absorption cross section: 10 -24 ~10 -20 cm -2 .

[0030] Further preferably, the thermal expansion coefficient of the doped zinc borate single crystal at 300K is lower than 4.0 / MK, preferably 2.5-3.5 / MK; the doped zinc borate single crystal has an isotropic thermal expansion coefficient; and / or the thermal conductivity of the doped zinc borate single crystal at 300K is higher than 20 W / m·K, preferably 25-35 W / m·K.

[0031] In the present invention, Mn 2+ The ions were doped into the zinc borate lattice by the method of the present invention, and large-sized high-quality ZBO:Mn 2+ Single crystal, fluorescence test shows that the ZBO:Mn 2+ The single crystal has optical properties superior to those of conventional laser crystals and a longer fluorescence lifetime than most other laser crystals (usually less than ~1ms), up to 10-20ms at room temperature at an emission wavelength of ~539nm, which is very beneficial for reducing the pump threshold for laser generation. It is worth noting that thermophysical measurements show that at room temperature, the ZBO:Mn 2+ The single crystal has the lowest thermal expansion coefficient and the highest thermal conductivity ( Figure 1 ) and the thermal expansion coefficient is isotropic. The use of this crystal can significantly improve the overall performance of the laser, and can effectively improve the power and quality of the output laser, and is suitable for high-power lasers and high-optical quality laser technology applications.

[0032] In a third aspect, the present invention provides a doped zinc borate single crystal obtained by the growth method of the doped zinc borate single crystal or the use of the doped zinc borate single crystal in a green light high-power laser device. The doped zinc borate single crystal provided by the present invention has excellent optical properties and can be well used as a laser crystal in the laser field. It has low thermal expansion (isotropy) and high thermal conductivity, can reduce the thermal effect of the laser crystal in high-power laser technology, and realize the output of high-power, high-quality laser. It is a laser crystal with excellent comprehensive performance.

[0033] In a fourth aspect, the present invention provides a laser crystal, wherein the laser crystal is a doped zinc borate single crystal obtained by the above-mentioned growth method of a doped zinc borate single crystal or the above-mentioned doped zinc borate single crystal. The doped zinc borate single crystal grown by the method of the present invention has obvious advantages over the thermal expansion coefficient and thermal conductivity of reported isotropic oxide and fluoride laser crystals, and has a higher thermal conductivity and a lower thermal expansion coefficient, and the thermal expansion coefficient is isotropic.

[0034] In a fifth aspect, the present invention provides a green light high-power laser device, which comprises the above-mentioned laser crystal. The doped zinc borate single crystal obtained by the growth method of the present invention can be better used as a high-performance green light laser crystal, and is suitable for various high-power laser devices.

[0035] The beneficial effects of the present invention are at least that: the Mn 2+ The doped zinc borate crystal optimizes its preparation process conditions and has the lowest thermal expansion coefficient (isotropic) and the highest thermal conductivity of all isotropic laser crystals reported so far, which significantly improves the thermal stability of the laser, has excellent optical and thermophysical properties, can effectively improve the power and quality of the output laser, and is suitable for high-power lasers and high-optical quality laser technology applications. The method provided by the present invention can solve the problem of laser power and quality reduction caused by the thermal effect of laser crystals in high-power laser technology without any other complicated processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. It is obvious that the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 A comparison of the thermal expansion coefficient and thermal conductivity of the provided doped zinc borate single crystal with reported isotropic oxide and fluoride laser crystals.

[0038] Figure 2 Schematic diagram of the crystal of the doped zinc borate single crystal provided in an embodiment of the present invention.

[0039] Figure 3 This is a fluorescence emission spectrum of the doped zinc borate single crystal provided in an embodiment of the present invention.

[0040] Figure 4 This is a fluorescence lifetime diagram of the doped zinc borate single crystal provided in an embodiment of the present invention.

[0041] Figure 5 This is a fluorescence excitation spectrum of the doped zinc borate single crystal provided in an embodiment of the present invention.

[0042] Figure 6 This is a thermal expansion curve of the doped zinc borate single crystal provided in an embodiment of the present invention.

[0043] Figure 7 This is a thermal conductivity diagram of the doped zinc borate single crystal provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] If no specific technology or conditions are specified in the embodiments of the present invention, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic product market.

[0046] Example 1

[0047] This embodiment provides a Mn 2+ Doped zinc borate single crystal (ZBO:Mn 2+ ), Mn 2+ The doping concentration is 3%.

[0048] The above-mentioned Mn provided in this embodiment 2+ The method for growing a doped zinc borate single crystal comprises the following steps:

[0049] 1) MnCO3, ZnO and B2O3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+, doping concentration 3%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1050°C at a rate of 1°C / min to melt the reagents, and the melt was stirred with a platinum stirring paddle at a stirring rate of 25 rpm for 7 days. The temperature was then reduced to 955°C at a rate of 1°C / h.

[0050] 2) The platinum wire was immersed 2 mm below the melt surface. During the crystal growth process, the cooling rate was set to 0.1°C / day. After the crystal growth lasted for 10 days, the platinum wire with the crystal was raised to 2 cm above the melt surface and the temperature was lowered to room temperature at a rate of 5°C / h.

[0051] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1050°C at a rate of 1°C / min to melt the reagent, stir the melt at a stirring rate of 25 rpm with a platinum stirring paddle for 7 days, then lower the melt temperature to 955°C at a rate of 1°C / h, immerse the seed crystal 2 mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.1°C / day and the seed crystal rotation speed to 10 rpm. After the crystal growth lasts for 10 days, raise the grown crystal to 2 cm above the melt surface and lower the temperature to room temperature at a rate of 5°C / h.

[0052] 4) By repeating step 3) for 7 times, ZBO:Mn 2+ Light green crystals ( Figure 2 ), size: 44×41×18mm 3 .

[0053] The 3% doping concentration ZBO:Mn prepared in this example 2+ The single crystal was tested for performance, and the test results are as follows:

[0054] 1) Emission spectrum: such as Figure 3 As shown, the emission peak center wavelength is 539nm, the emission peak half-peak width is 40nm, and the emission cross section is 4.54×10 -23 cm -2 ;like Figure 4 As shown, fluorescence lifetime: 16.66ms.

[0055] 2) Excitation spectrum: Figure 5 As shown, the excitation peaks are: 421nm, 427nm, 445nm, and the absorption cross sections corresponding to the three peaks are: 3.34×10 -22 cm -2 , 4.16×10 -22 cm -2 , 2.73×10 -22 cm -2 .

[0056] 3) Thermophysical properties: such as Figure 6 As shown, at 300K: thermal expansion coefficient 3.01 / MK, isotropic; Figure 7 As shown, at 300K: thermal conductivity 28.80W / (m·K).

[0057] Example 2

[0058] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0059] 1) MnCO3, ZnO and B2O3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+ , doping concentration 1%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1080°C at a rate of 2°C / min to melt the reagents, and the melt was stirred with a platinum stirring paddle at a stirring rate of 20 rpm for 6 days. The temperature was then reduced to 954°C at a rate of 2°C / h.

[0060] 2) The platinum wire was immersed 1 mm below the melt surface. During the crystal growth process, the cooling rate was set to 0.2°C / day. After the crystal growth lasted for 7 days, the platinum wire with the crystal was raised to 1 cm above the melt surface and the temperature was lowered to room temperature at a rate of 12°C / h.

[0061] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1080°C at a rate of 2°C / min to melt the reagent, stir the melt at a stirring rate of 20rpm with a platinum stirring paddle for 6 days, then lower the melt temperature to 954°C at a rate of 2°C / h, immerse the seed crystal 1mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.2°C / day and the seed crystal rotation speed to 15rpm. After the crystal growth lasts for 7 days, raise the grown crystal to 1cm above the melt surface and lower the temperature to room temperature at a rate of 12°C / h.

[0062] 4) By repeating step 3) for 4 times, ZBO:Mn 2+ Light green crystals, size 40×40×16mm 3 .

[0063] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 41nm, emission cross section: 6.53×10 -23 cm -2 , fluorescence lifetime: 15.22ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks:

[0064] 4.34×10 -22 cm -2 , 4.36×10 -22 cm -2 , 2.67×10 -22 cm -2 . 3) Thermophysical properties: at 300K: thermal expansion coefficient 3.14 / MK, isotropic; at 300K: thermal conductivity 28.56W / (m·K).

[0065] Example 3

[0066] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0067] 1) MnCO3, ZnO and B2O3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+ , doping concentration 5%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1070°C at a rate of 1.5°C / min to melt the reagents, and the melt was stirred with a platinum stirring paddle at a stirring rate of 18 rpm for 5 days. The temperature was then reduced to 956°C at a rate of 3°C / h.

[0068] 2) The platinum wire was immersed 3 mm below the melt surface. During the crystal growth process, the cooling rate was set to 0.3 °C / day. After the crystal growth lasted for 8 days, the platinum wire with the crystal was raised to 2 cm above the melt surface and the temperature was lowered to room temperature at a rate of 15 °C / h.

[0069] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1070°C at a rate of 1.5°C / min to melt the reagent, stir the melt with a platinum stirring paddle at a stirring rate of 18rpm for 5 days, then lower the melt temperature to 956°C at a rate of 3°C / h, immerse the seed crystal 3mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.3°C / day and the seed crystal rotation speed to 15rpm. After the crystal growth lasts for 8 days, raise the grown crystal to 2cm above the melt surface and lower the temperature to room temperature at a rate of 15°C / h.

[0070] 4) By repeating step 3) for 4 times, ZBO:Mn 2+ Light green crystals, 38×35×14mm in size 3 .

[0071] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 38nm, emission cross section: 3.45×10 -23 cm -2 , fluorescence lifetime: 15.67ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks: 3.74×10 -22 cm -2 , 5.35×10 -22 cm -2 , 2.67×10 -22 cm -2 . 3) Thermal physical properties: at 300K: thermal expansion coefficient 3.34 / MK, isotropic; at 300K: thermal conductivity 29.44W / (m·K).

[0072] Example 4

[0073] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0074] 1) MnCO3, ZnO and B2O3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+ , doping concentration 6%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1040°C at a rate of 2°C / min to melt the reagents, and the melt was stirred at a stirring rate of 34 rpm with a platinum stirring paddle for 5 days. The temperature was then lowered to 955°C at a rate of 5°C / h.

[0075] 2) The platinum wire is immersed 1 mm below the melt surface. During the crystal growth process, the cooling rate is set to 0.2°C / day. After the crystal growth continues for 6 days, the platinum wire with the crystal is raised to 4 cm above the melt surface and the temperature is lowered to room temperature at a rate of 6°C / h.

[0076] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1040°C at a rate of 2°C / min to melt the reagent, stir the melt at a stirring rate of 34rpm with a platinum stirring paddle for 5 days, then lower the melt temperature to 955°C at a rate of 5°C / h, immerse the seed crystal 1mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.2°C / day and the seed crystal rotation speed to 15rpm. After the crystal growth lasts for 6 days, raise the grown crystal to 4cm above the melt surface and lower the temperature to room temperature at a rate of 6°C / h.

[0077] 4) By repeating step 3) for 5 times, ZBO:Mn 2+Light green crystals, 38×41×17mm in size 3 .

[0078] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 40nm, emission cross section: 7.56×10 -23 cm -2 , fluorescence lifetime: 15.84ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks: 5.67×10 -22 cm -2 , 4.89×10 -22 cm -2 , 6.61×10 -22 cm -2 . 3) Thermal physical properties: at 300K: thermal expansion coefficient 3.03 / MK, isotropic; at 300K: thermal conductivity 29.89W / (m·K).

[0079] Example 5

[0080] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0081] 1) MnCO3, ZnO and B2O3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+ , doping concentration 0.5%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1090°C at a rate of 1°C / min to melt the reagents, and the melt was stirred at a stirring rate of 30 rpm with a platinum stirring paddle for 4 days. The temperature was then lowered to 955°C at a rate of 2°C / h.

[0082] 2) The platinum wire is immersed 3 mm below the melt surface. During the crystal growth process, the cooling rate is set to 0.1°C / day. After the crystal growth continues for 10 days, the platinum wire with the crystal is raised to 1 cm above the melt surface and the temperature is lowered to room temperature at a rate of 8°C / h.

[0083] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1090°C at a rate of 1°C / min to melt the reagent, stir the melt at a stirring rate of 30rpm with a platinum stirring paddle for 4 days, then lower the melt temperature to 955°C at a rate of 2°C / h, immerse the seed crystal 3mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.1°C / day and the seed crystal rotation speed to 8rpm. After the crystal growth lasts for 10 days, raise the grown crystal to 1cm above the melt surface and lower the temperature to room temperature at a rate of 8°C / h.

[0084] 4) By repeating step 3) for 3 times, ZBO:Mn 2+ Light green crystals, 44×43×21mm in size 3 .

[0085] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 41nm, emission cross section: 9.51×10 -23 cm -2 , fluorescence lifetime: 18.25ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks:

[0086] 5.64×10 -22 cm -2 , 4.31×10 -22 cm -2 , 3.33×10 -22 cm -2 . 3) Thermal physical properties: at 300K: thermal expansion coefficient 3.22 / MK, isotropic; at 300K: thermal conductivity 30.77W / (m·K).

[0087] Example 6

[0088] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0089] 1) MnCO3, ZnO and B2O3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+ , doping concentration 0.8%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1030°C at a rate of 1°C / min to melt the reagents, and the melt was stirred with a platinum stirring paddle at a stirring rate of 20 rpm for 4 days. The temperature was then reduced to 957°C at a rate of 2°C / h.

[0090] 2) The platinum wire was immersed 2 mm below the melt surface. During the crystal growth process, the cooling rate was set to 0.5°C / day. After the crystal growth lasted for 6 days, the platinum wire with the crystal was raised to 4 cm above the melt surface and the temperature was lowered to room temperature at a rate of 9°C / h.

[0091] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1030°C at a rate of 1°C / min to melt the reagent, stir the melt at a stirring rate of 20rpm with a platinum stirring paddle for 4 days, then lower the melt temperature to 957°C at a rate of 2°C / h, immerse the seed crystal 2mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.5°C / day and the seed crystal rotation speed to 15rpm. After the crystal growth lasts for 6 days, raise the grown crystal to 4cm above the melt surface and lower the temperature to room temperature at a rate of 9°C / h.

[0092] 4) By repeating step 3) for 4 times, ZBO:Mn 2+ Light green crystals, 38×41×15mm in size 3 .

[0093] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 40nm, emission cross section: 7.56×10 -23 cm -2 , fluorescence lifetime: 19.54ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks: 5.44×10 -22 cm -2 , 3.45×10 -22 cm -2 , 6.78×10 -22 cm -2 . 3) Thermophysical properties: at 300K: thermal expansion coefficient 3.31 / MK, isotropic; at 300K: thermal conductivity 29.78W / (m·K).

[0094] Example 7

[0095] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0096] 1) MnCO3, Zn2(OH)2CO3 and H3BO3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+ , doping concentration 3%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1050°C at a rate of 1°C / min to melt the reagents, and the melt was stirred with a platinum stirring paddle at a stirring rate of 35 rpm for 7 days. The temperature was then lowered to 955°C at a rate of 1°C / h.

[0097] 2) The platinum wire was immersed 1 mm below the melt surface. During the crystal growth process, the cooling rate was set to 0.1°C / day. After the crystal growth lasted for 10 days, the platinum wire with the crystal was raised to 1 cm above the melt surface and the temperature was lowered to room temperature at a rate of 6°C / h.

[0098] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1050°C at a rate of 1°C / min to melt the reagent, stir the melt at a stirring rate of 35 rpm with a platinum stirring paddle for 7 days, then lower the melt temperature to 955°C at a rate of 1°C / h, immerse the seed crystal 1 mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.1°C / day and the seed crystal rotation speed to 8 rpm. After the crystal growth lasts for 10 days, raise the grown crystal to 1 cm above the melt surface and lower the temperature to room temperature at a rate of 6°C / h.

[0099] 4) By repeating step 3) for 4 times, ZBO:Mn 2+ Light green crystals, 38×38×15mm in size 3 .

[0100] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 38nm, emission cross section: 9.77×10 -24 cm -2 , fluorescence lifetime: 16.78ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks: 8.56×10 -23 cm -2 , 7.78×10 -23 cm -2 , 4.55×10 -23 cm -2 . 3) Thermophysical properties: at 300K: thermal expansion coefficient 3.24 / MK, isotropic; at 300K: thermal conductivity 29.67W / (m·K).

[0101] Example 8

[0102] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0103] 1) MnO, Zn2(OH)2CO3 and H3BO3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+, doping concentration 3%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1050°C at a rate of 1°C / min to melt the reagents, and the melt was stirred with a platinum stirring paddle at a stirring rate of 40 rpm for 7 days. The temperature was then reduced to 955°C at a rate of 1°C / h.

[0104] 2) The platinum wire was immersed 1 mm below the melt surface. During the crystal growth process, the cooling rate was set to 0.1°C / day. After the crystal growth lasted for 10 days, the platinum wire with the crystal was raised to 2 cm above the melt surface and the temperature was lowered to room temperature at a rate of 6°C / h.

[0105] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1050°C at a rate of 1°C / min to melt the reagent, stir the melt with a platinum stirring paddle at a stirring rate of 40rpm for 7 days, then lower the melt temperature to 955°C at a rate of 1°C / h, immerse the seed crystal 1mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.1°C / day and the seed crystal rotation speed to 18rpm. After the crystal growth lasts for 10 days, raise the grown crystal to 2cm above the melt surface and lower the temperature to room temperature at a rate of 6°C / h.

[0106] 4) By repeating step 3) for 4 times, ZBO:Mn 2+ Light green crystals, 41×41×19mm in size 3 .

[0107] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 40nm, emission cross section: 1.53×10 -21 cm -2 , fluorescence lifetime: 16.31ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks: 5.77×10 -20 cm -2 ,7.33×10 -21 cm -2 , 1.63×10 -20 cm -2 . 3) Thermophysical properties: at 300K: thermal expansion coefficient 3.21 / MK, isotropic; at 300K: thermal conductivity 29.98W / (m·K).

[0108] Example 9

[0109] This embodiment provides a Mn 2+ The specific steps of the growth method of the doped zinc borate single crystal are as follows:

[0110] 1) MnCO3, Zn2(CH3COO)2·2H2O and B2O3 with a purity of 99.99% were prepared according to the formula (ZBO:Mn 2+ , doping concentration 3%) molar ratio was fully ground and mixed, then filled into a platinum crucible with a diameter of 100 mm and placed in a programmed crystal growth furnace. The temperature was raised to 1050°C at a rate of 1°C / min to melt the reagents, and the melt was stirred with a platinum stirring paddle at a stirring rate of 25 rpm for 7 days. The temperature was then reduced to 955°C at a rate of 1°C / h.

[0111] 2) The platinum wire was immersed 3 mm below the melt surface. During the crystal growth process, the cooling rate was set to 0.1°C / day. After the crystal growth lasted for 10 days, the platinum wire with the crystal was raised to 3 cm above the melt surface and the temperature was lowered to room temperature at a rate of 6°C / h.

[0112] 3) Cut off the transparent and uniform part of the grown crystal and use it as a seed crystal. Raise the temperature to 1050°C at a rate of 1°C / min to melt the reagent, stir the melt with a platinum stirring paddle at a stirring rate of 25 rpm for 7 days, then lower the melt temperature to 955°C at a rate of 1°C / h, immerse the seed crystal 3mm below the melt surface, and during the crystal growth process, set the cooling rate to 0.1°C / day and the seed crystal rotation speed to 16rpm. After the crystal growth lasts for 10 days, raise the grown crystal to 3cm above the melt surface and lower the temperature to room temperature at a rate of 6°C / h.

[0113] 4) By repeating step 3) for 5 times, ZBO:Mn 2+ Light green crystals, size 42×42×18mm 3 .

[0114] The test results of this embodiment are as follows: 1) Emission spectrum: emission peak center wavelength: 539nm, emission peak half-peak width: 39nm, emission cross section: 4.13×10 -23 cm -2 , fluorescence lifetime: 18.67ms. 2) Excitation spectrum: Excitation peaks: 421nm, 427nm, 445nm, corresponding absorption cross sections of the three peaks: 5.54×10 -22 cm -2 , 3.21×10 -22 cm -2 , 5.68×10 -22 cm -2 . 3) Thermal physical properties: at 300K: thermal expansion coefficient 3.43 / MK, isotropic; at 300K: thermal conductivity 32.98W / (m·K).

[0115] Comparative Example 1

[0116] This comparative example provides a doped zinc borate glass, which is prepared by the method of invention CN1785865A. The manganese-doped long afterglow glass provided in comparative example 1 is prepared by a melting and quenching method (accurately weighing the raw materials in proportion, grinding and mixing, melting in a high-temperature furnace, adding elemental zinc as a reducing agent or forming a reducing atmosphere in the furnace, pouring the glass into a mold after it is taken out of the furnace, annealing and cooling naturally), and the preparation method is different from the slow cooling crystallization method of the present invention. Moreover, from the perspective of microstructure, glass only has a short order and no long order; while crystals have both short and long orders. Due to the difference in microstructure, the manganese-doped zinc borate single crystal provided by the present invention emits green light (central wavelength ~ 539 nanometers), while the manganese-doped zinc borate glass provided in comparative example 1 emits red light (central wavelength ~ 600 nanometers). At the same time, comparative example 1 does not involve the thermal conductivity data of manganese-doped zinc borate glass, but from the perspective of the structure-performance relationship of thermal conductivity, the disordered structure inside the glass will produce strong scattering of the carrier of heat propagation-phonon, and its thermal conductivity will be lower than that of the crystal. The manganese-doped zinc borate glass given in Comparative Example 1 does not have the high thermal conductivity of the manganese-doped zinc borate single crystal provided by the present invention, and cannot be used as a working medium for high-power, high-quality laser generation.

[0117] Comparative Example 2

[0118] This comparative example provides a use of zinc borate crystals in laser crystals (CN 107740179A). The doping ions (i.e., activation ions) used in the present invention are manganese ions, while the activation ions used in Comparative Example 2 are neodymium ions, thulium ions, ytterbium ions, erbium ions, or titanium ions. Due to the different doping ions, the luminescence characteristics of the crystals provided in Comparative Example 2 are also different from those of the crystals provided in the present invention. The crystals provided in Comparative Example 2 do not have the optical parameter indicators of the manganese-doped zinc borate single crystals provided by the present invention for use as laser crystals. In addition, the present invention adopts a crystal growth method of directly mixing and melting the raw materials, while Comparative Example 2 adopts a crystal growth method of "solid phase synthesis first, then melt growth". The present invention is simpler than the crystal growth method of Comparative Example 2.

[0119] Comparative Example 3

[0120] This comparative example provides a Zn4B6O 13 Single crystal growth method (CN 114457423 A). Comparative Example 3 provides Zn4B6O 13 The single crystal has no doping ions and does not have the performance to be used as a laser crystal. In addition, in the crystal growth method provided by the present invention, in addition to providing ZBO:Mn 2+Except for the necessary manganese source, zinc source and boron source of the elements contained in the single crystal, no other reagents are used, while the comparative example 3 adopts the growth method of the co-solvent, and in addition to the necessary zinc source and boron source, one or more of the co-solvents LiF, NaF, KF, RbF, CsF or ZnF2 need to be added. Compared with the comparative example 3, the present invention does not need to introduce other reagents, the crystal growth method is simpler, and the obtained crystal does not contain impurity atoms and has better performance.

[0121] Comparative Example 4

[0122] This comparative example provides a method for preparing large-sized Zn4B6O 13 Single crystal method (CN 108221052A). Comparative Example 4 provides Zn4B6O 13 There are no doped ions in the single crystal, and it does not have the performance to be used as a laser crystal. In addition, the present invention adopts a crystal growth method of directly mixing and melting the raw materials, while the crystal growth method of "precursor I-precursor II-polycrystalline material-single crystal growth" is adopted in Comparative Example 4. The crystal growth method of the present invention is simpler than that of Comparative Example 4.

[0123] Comparative Example 5

[0124] This comparative example provides a method for preparing large-sized Zn4B6O 13 Single crystal method (Xingxing Jiang et alNear-Zero Thermal Expansion and High Ultraviolet Transparency in a BorateCrystal of Zn4B6O 13 . "Advanced Materials". 2016, Vol. 28, No. 201601816). Comparative Example 5 provides Zn4B6O 13 There are no doped ions in the single crystal, and it does not have the performance to be used as a laser crystal. In addition, the present invention adopts a crystal growth method of directly mixing and melting the raw materials, while Comparative Example 5 adopts a crystal growth method of "solid phase synthesis-single crystal growth". Compared with the crystal growth method of Comparative Example 5, the present invention is simpler and the grown crystal has excellent performance.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for growing a doped zinc borate single crystal, characterized in that: include: 1) Preparation of ZBO:Mn 2+ melt: mixing raw materials containing manganese, zinc and boron, heating to a first temperature, stirring, and cooling to a second temperature to obtain a melt; 2) Crystal growth: the platinum wire is immersed below the liquid surface of the melt and then slowly cooled, and the platinum wire with the crystal grown thereon is taken out of the melt and then subjected to a first cooling process; 3) Secondary growth of crystals: all or part of the crystals obtained in step 2) are used as seed crystals, immersed below the liquid surface of the melt, the seed crystal rotation speed is set and the temperature is slowly reduced, and the crystals are taken out of the melt and then subjected to a second cooling process; 4) Repeated crystal growth: using all or part of the crystal obtained in step 3) as a seed crystal, repeating the crystal growth process of step 3) at least once.

2. The method for growing a doped zinc borate single crystal according to claim 1, characterized in that: In step 1), the first temperature is 1000-1100° C.; the temperature is raised to 1000-1100° C. at a rate of 0.5-5° C. / min, and stirred at a stirring rate of 5-50 rpm with a platinum stirring paddle for 2-10 days; And / or, in step 1), the second temperature is 900-1000°C; the temperature is reduced to 900-1000°C at a rate of 0.1-20°C / h; And / or, in step 1), in the raw materials, the manganese source is MnCO3 and / or MnO, the zinc source is ZnO, Zn2(OH)2CO3 and / or Zn2(CH3COO)2·2H2O, and the boron source is B2O3 and / or H3BO3; the ZBO:Mn 2+ Zn4B6O 13 :Mn 2+ , Mn 2+ The ion doping concentration is 0.1%~30%.

3. The method for growing a doped zinc borate single crystal according to claim 1, characterized in that: In step 2), the mixture is immersed 1 to 5 mm below the liquid surface of the melt; And / or, in step 2), the slow cooling is cooling at a rate of 0.1-1°C / day for 3-20 days; And / or, in step 2), the platinum wire with the crystals grown thereon is taken out from the melt, and the platinum wire with the crystals grown thereon is taken out to 1 to 5 cm above the melt surface; And / or, in step 2), the first cooling is to cool to room temperature at a rate of 1-20°C / h.

4. The method for growing a doped zinc borate single crystal according to any one of claims 1 to 3, characterized in that: In step 3), the mixture is immersed 1 to 5 mm below the liquid surface of the melt; And / or, in step 3), the rotation speed of the seed crystal is 1-30 rpm, and the slow cooling is cooling at a rate of 0.1-1°C / day for 3-20 days; and / or, in step 3), taking out the crystal from the melt, and raising the grown crystal to 1 to 5 cm above the melt surface; And / or, in step 3), the second cooling is to cool to room temperature at a rate of 1-20°C / h; And / or, step 3) further comprises heating the raw material reagent cooled in step 2) to the first temperature again, stirring it, and cooling it to the second temperature to obtain a melt again; and / or, in step 3) and / or step 4), using a transparent and uniform portion of the grown crystal as a seed crystal; And / or, in step 4), repeating the crystal growth process 1 to 10 times.

5. A doped zinc borate single crystal, characterized in that: The zinc borate-doped single crystal is obtained by the growth method of any one of claims 1 to 4.

6. The doped zinc borate single crystal according to claim 5, characterized in that: The doped zinc borate single crystal has green light emission under ultraviolet light irradiation; the luminescence performance of the doped zinc borate single crystal is as follows: emission peak central wavelength: 530-550nm, emission peak half-peak width: 30-50nm, excitation band: 200-500nm, fluorescence lifetime at 300K: 10-20ms, emission cross section: 10 -25 ~10 - 21 cm -2 , absorption cross section: 10 -24 ~10 -20 cm -2 .

7. The doped zinc borate single crystal according to claim 5 or 6, characterized in that: The thermal expansion coefficient of the doped zinc borate single crystal at 300K is lower than 4.0 / MK; the doped zinc borate single crystal has an isotropic thermal expansion coefficient; and the thermal conductivity of the doped zinc borate single crystal at 300K is higher than 20W / m·K.

8. Use of the doped zinc borate single crystal obtained by the growth method of the doped zinc borate single crystal according to any one of claims 1 to 4 or the doped zinc borate single crystal according to any one of claims 5 to 7 in a green light high-power laser device.

9. A laser crystal, characterized in that: The laser crystal is a doped zinc borate single crystal obtained by the growth method of a doped zinc borate single crystal according to any one of claims 1 to 4 or a doped zinc borate single crystal according to any one of claims 5 to 7.

10. A green light high-power laser device, characterized in that: The laser crystal according to claim 9 is included.

Citation Information

Patent Citations

  • Method for preparing large-size Zn4B6O13 single crystal

    CN108221052A

  • Growth method of Zn4B6O13 single crystal

    CN114457423A

  • Laser crystal ErBa3B9O18 of borate, preparation method, and usage

    CN101092745A

  • Application of zinc borate crystal in laser crystal

    CN107740179A

  • Preparation method of red or green long afterglow glass using zinc borate as substrate

    CN1785865A